Marketing: An Introduction - Philip Kotler; Gary M. Armstrong; Marc Oliver Opresnik (United Kingdom Pearson Education Limited, 2020)
How do we get you moving? By placing you-the customer-in the driver's seat. Marketing introduces the leading marketing thinking on how customer value is the driving force behind every marketing strategy.
Keywords: Marketing; Textbooks; Management; Business; (MGT-103) Understanding Markets and Marketing